2019
DOI: 10.1002/jlcr.3791
|View full text |Cite
|
Sign up to set email alerts
|

Improved synthesis of 4‐[18F]fluoro‐m‐hydroxyphenethylguanidine using an iodonium ylide precursor

Abstract: Fluorine-18 labeled hydroxyphenethylguanidines were recently developed in our laboratory as a new class of PET radiopharmaceuticals for quantifying regional cardiac sympathetic nerve density in heart disease patients. Studies of 4-[ 18 F]fluoro-m-hydroxyphenethylguanidine ([ 18 F]4F-MHPG) and 3-[ 18 F] fluoro-p-hydroxyphenethylguanidine ([ 18 F]3F-PHPG) in human subjects haveshown that these radiotracers can be used to generate high-resolution maps of regional sympathetic nerve density using the Patlak graphic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…In exploring new methods that offer higher yield, spirocyclic iodonium ylide rather than 2-thienyl iodonium salt precursor has been used due to the even higher electron density offered by the former moiety, which could lead to higher yield. Under optimized automated reaction conditions, the yield increased threefold, averaging 7.8%, which the authors claimed being well suited to on-site production for clinical PET studies (Jung et al 2019).…”
Section: F-4f-mhpg and 3f-phpgmentioning
confidence: 99%
See 1 more Smart Citation
“…In exploring new methods that offer higher yield, spirocyclic iodonium ylide rather than 2-thienyl iodonium salt precursor has been used due to the even higher electron density offered by the former moiety, which could lead to higher yield. Under optimized automated reaction conditions, the yield increased threefold, averaging 7.8%, which the authors claimed being well suited to on-site production for clinical PET studies (Jung et al 2019).…”
Section: F-4f-mhpg and 3f-phpgmentioning
confidence: 99%
“…For example, LogP, or polar surface area, which can be determined by comparing the biodistribution data of 4F-MHPG with MIBG and HED (Jang et al 2013a). Of note, when evaluating the biodistribution and kinetics (Jang et al 2013a, b;Jung et al 2017Jung et al , 2019. This figure was created using ChemDraw 16 for Mac of 18 F-AF78 in different animal species, cardiac uptake showed significant differences (unpublished data): it showed different modes of cardiac uptake in animals with only the uptake-1 mechanism, i.e.…”
Section: F-af78mentioning
confidence: 99%
“…In line with previous studies on SCIDY radiofluorination, prolonged reaction times or elevated base concentrations above the optimal range of 4−6 equiv had deleterious effects on precursor stability and RCY (Figure 2B). 22,35,37 Higher overall yields were observed in dimethyl sulfoxide (DMSO) after 10 min (55 ± 9%) compared to DMF (Figure 2A), while replacing TEAB with potassium carbonate and Kryptofix (K 2 CO 3 /K 2.2.2 ) led to markedly lower yields in either solvent (<7%, Table S2). Nearly quantitative disappearance of protected intermediate [ 18 F]5 in the presence of 12 M HCl was observed after 5 min to form the desired product [ 18 F]6 ([ 18 F]mFBG).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…More recently, radiotracer candidates bearing a phenethylguanidine core (Figure ) have exhibited slower neuronal uptake rates in human imaging, while maintaining irreversible kinetics due to vesicular trapping mediated by vesicular monoamine transporter 2 (VMAT2) . Initial challenges associated with nucleophilic 18 F-fluorination of the electron-rich aromatic rings in 4-[ 18 F]­fluoro- meta -hydroxyphenethylguanidine ([ 18 F]­4F-MHPG) have since been overcome using spirocyclic iodonium ylide radiofluorination. ,, Nevertheless, [ 18 F]­4F-MHPG and its isomer [ 18 F]­3F-PHPG inspired the development of [ 18 F]­AF78, which retains the phenethylguanidine core with an appended 3-fluoropropyl ether moiety for more facile radiolabeling . Preliminary studies with [ 18 F]­AF78 have demonstrated cardiac retention in rats likely due to extraneuronal uptake mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…利用该 方法可有效地对结构多样(包括酯、氨基甲酸酯、卤化 物、酰胺、硝基、三氟甲基、酮和杂环)的各种非活性 芳烃进行放射性标记, 合成了一系列多功能分子和 18 F 标记的放射性化合物(Scheme 39, a). 2015 年, Vasdev 与 Liang 等 [63][64] 实现了采用连续流动微流控技术进行上述 [65] 使用螺环碘叶 立德作为前体合成了一类新的 PET 放射性药物-- 18 氟标记的羟苯乙基胍 183 和 184 (Scheme 39, c). 总而 言之, 碘叶立德的放射性氟化反应被证明是合成 18 F 标记的放射性药物的一种有效方法.…”
Section: 卤化反应unclassified